TERRITORIAL AND NON-TERRITORIAL AUTONOMY: “ROMANIAN PARADOX” - CRISTIAN JURA (Challenges of the Knowledge Society)
Whereas in Romania there are 19 national minorities officially acknowledged by Romanian state, up to present, one did not manage to adopt a special law of national minorities. We identify special disposals related to national minorities in Romanian Constitution, in the law of local public administration, the law of education, the law concerning the election of the Chamber of Deputies and Senate, the law related to political parties, the law for the election of the authorities of local public administration, the law concerning the combating of all forms of discrimination. In the last project of the Law concerning the statute of national minorities in Romania, a new concept is introduced: cultural autonomy of minorities. The cultural autonomy is a form of non-territorial autonomy. Nevertheless, Romania is criticised by some international organisations for the fact that the organisations of national minorities represented in the Parliament of Romania have instituted a monopole, therefore no other organisation of any minority is allowed to participate to the elections.